Sellaphora pelagonica (Bacillariophyceae), a new species from dystrophic ponds in the Republic of North Macedonia - KOCHOSKA, HRISTINA; ZAOVA, DUŠICA; VIDESKA, ANASTASIJA; MITIC-KOPANJA, DANIJELA; NAUMOVSKA, HRISTINA; WETZEL, CARLOS E.; ECTOR, LUC; LEVKOV, ZLATKO (Magnolia Press, 2021)
Lowland intermittent ponds, although biologically important, are poorly studied water habitats. During the analyses of the material taken from lowland pond in Pelagonia Valley, and Vitachevo, Republic of North Macedonia, the diatom Sellaphora pelagonica sp. nov. was recorded and described based on light and scanning electron microscopy. The species is characterized by a strictly linear valve outline with parallel to slightly concave margins and broadly rounded ends, 15.0–40.0 µm long and 5.0–7.0 µm wide. These features, together with raphe structure and areolar shape are compared with several similar taxa currently ascribed to Sellaphora.
Keywords: diatom, freshwater, lowland ponds, Pelagonia, taxonomy